SPECIAL CHARACTERISTICS OF TREATMENT OF SEVERE ATOPIC DERMATITIS IN CHILDREN - D. Sh. Macharadze ("Paediatrician" Publishers LLC, 2013)
The article analyzes modern data on risk factors of severe course of atopic dermatitis in children: the role of alimentary and inhalant allergens, cutaneous infections, allergic reactions to drugs used in the treatment of disease. The most important questions of differential diagnosis of atopic dermatitis in children and the distinctive features of the illness, which may be mistaken for atopic dermatitis (primary immunodeficiencies, keratosis pilaris, psoriasis, enteropatic acrodermatitis; cutaneous bacterial and fungal infections, and drug-induced contact dermatitis to topical creams and ointments) are discussed. Treatment of atopic dermatitis is based on modern approaches and includes recommendations on the use of emolents, anti-inflammatory drugs (topical glucocorticoids) and calcineurin inhibitors. The article provides indications and contraindications to the administration of anti-inflammatory drugs. Special recommendations for use of cleansers and emolents at all degrees of severity of atopic dermatitis, which helps reduce the risk of side effects of topical corticosteroids, complications such as cutaneous infections and helps to maintain remission of disease are given. The importance of training programs patients is emphasized. Compliance of patients and/or their parents contributes to the achievement of the desired effect of the treatment of atopic dermatitis, which will improve the patients' quality of life.